Pengaruh Electronic Word Of Mouth (E-WOM) Dan Brand Experience Terhadap Loyalitas Pelanggan Melalui Keputusan Pembelian Sebagai Variabel Intervening Produk Skincare Y.O.U (Studi Kasus Pada Generasi Z Kota Malang) - Pertiwi, Ria Dwi Ayu; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to examine and analyze the influence of Electronic Word of Mouth and Brand Experience on Customer Loyalty through Purchase Decision as an intervening variable in the case of Y.O.U skincare products among Generation Z in Malang City. This study employs a descriptive quantitative approach, with data collected through questionnaires. The sampling technique used is purposive sampling. The data analysis method applied in this research is Structural Equation Modeling - Partial Least Square (SEM-PLS) 3. The results indicate that Electronic Word of Mouth and Brand Experience have a significant influence on Purchase Decision. However, Electronic Word of Mouth does not affect Customer Loyalty, while Brand Experience significantly influences Customer Loyalty. Additionally, Purchase Decision mediates the relationship between Electronic Word of Mouth and Brand Experience on Customer Loyalty.  Keywords: Electronic Word Of Mouth, Brand Experiance, Purchase Decision, Customer Loyalty.